Plant density, pruning of the lower lateral branches, and production of two cultivars of coffea Arabica and of hybrid ’Icatu’ - Siqueira, R.; Filho, A. Androcioli; Pavan, M.A.; Chaves, J.C. D. (Pesquisa Agropecuaria Brasileira, 2014)
In 1976 two coffee cultivars Catuaí-Vermelho and Acaiá (Coffea arabica L.) and one hybrid 'Icatu' (Coffea arabica x Coffea canephora) were planted in Londrina, State of Paraná, Brazil, to determine the effects of spacing between plants in the row and pruning the lower lateral branches, on the coffee production during the next six years. Four coffee yielding records were taken for the period 1978 to 1981. Yields increased per area with increasing plant density. The total yields of clean coffee for Catuaí-Vermelho, Icatu, and Acaiá for the period were 4.920, 4.080, and 3.902 kg/ha for rows spaced 4 m x 1 m and 4,294, 3,759 and 3,174 kg/ha for rows spaced 4 m x 2 m, respectively. For the first two years of production, yield for Acaiá was higher than for Catuaí-Vermelho and Icatu as the distances between plants were decreased. Yield was not affected by pruning, with exception of 1978. On July 20, 1981, the coffee plants were injured by a severe frost with minima temperature below -0.2ºC. The results indicate significant differences between the Catuaí-Vermelho and Acaiá cultivars regarding the level of coffee production in 1981 and the recovery and subsequent growth of coffee plants after frost in 1981.